Radio Electric Asymmetric Conveyer: A Novel Neuromodulation Technology in Alzheimer’s and Other Neurodegenerative Diseases - Rinaldi, Salvatore; Calzà, Laura; Giardino, Luciana; Biella, Gabriele E. M.; Zippo, Antonio G.; Fontani, Vania (Frontiers in Psychiatry, 2015)
Global research in the field of pharmacology has not yet found effective drugs to treat Alzheimer's disease. Thus, alternative therapeutic strategies are under investigation, such as neurostimulation by physical means. Radio electric asymmetric conveyer (REAC) is one of these technologies and has, until now, been used in clinical studies on several psychiatric and neurological disorders with encouraging results in the absence of side effects. Moreover, studies at the cellular level have shown that REAC technology, with the appropriate protocols, is able to induce neuronal differentiation both in murine embryonic cells and in human adult differentiated cells. Other studies have shown that REAC technology is able to positively influence senescence processes. Studies conducted on Alzheimer's disease (AD) patients and in transgenic mouse models have shown promising results, suggesting REAC could be a useful therapy for certain components of AD.